Water consumption of South African vineyards : a modelling approach based on the quantified combined effects of selected viticultural, soil and meteorological parameters - Myburgh, P. A. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1998.